Análise das capacidades perceptivo-motoras, físicas e cognitivas de idosos praticantes de hidroginástica - Estivalet, Kátine Marchezan (2016)
INTRODUCTION: Ageing is a process that causes organic and functional alterations, compromising elements from perceptual-motive, physical, and cognitive capabilities, that can interfere in the occupational performance of elderly people. However, physical exercises, such as water aerobics, have positive effects in the biological, psychological, and social aspects, especially in the search for an active ageing. OBJECTIVE: The main goal of this study is to analyze the perceptual-motive, physical, and cognitive capabilities, as well as the occupational performance of elderly people who practice water aerobics and the possible correlations between the variables. METHODOLOGY: In order to do that, individuals aged 60 years old or older, associated to the Physical Activities Project for Elderly Water Aerobics , from the Physical Education and Sports Center of the Federal University of Santa Maria, were selected. For the descriptive analysis of data, mean and standard deviation were used, and the correlation of Pearson and Multivariate Analysis were used to identify the correlations between the variables. RESULTS: Through the descriptive analysis of the variables, it was noticed that the simple reaction time for visual stimuli is faster than the auditory stimuli; that the dominant hand presents better fine motor skills and higher manual gripping force; besides the perception of satisfaction being better than the occupational performance itself. In the multivariate analysis, it was noticed a stronger correlation between the elements of precision of arm-hand movement, followed by the correlation between simple reaction time and cognitive functions (attention and concentration). In this study, there was also a significant correlation between the performance and the satisfaction of elderly (r=000.7 and p ≥0,001). The most problematic area of performance was self-care, especially because of the difficulty in functional mobility, and the practice of another physical exercise as active recreation was mentioned as the most important problem-activity in leisure area. CONCLUSION: With this study, it was possible to investigate the behavior of the perceptive-motive capabilities: fine motor skills, reaction time, and peripheral perception; the cognitive capabilities: attention and concentration; the manual gripping-force; besides evaluating the occupational development of elderly who practice water aerobics and the relation between those variables.